UPAYA PENYATUAN KALENDER ISLAM INTERNASIONAL OLEH ORGANISASI KERJASAMA ISLAM (OKI) - Hamdun (Direktorat Jenderal Bimbingan Masyarakat Islam, 2017)
The Islamic Calendar system is an important element in Islamic civilization. The existence of the Islamic Calendar since the last 14 centuries has the function of marking the various events of Muslim life such as worship and daily activities. However, after being used for 1,400 years, the Islamic Calendar system have not be used uniformly in the Islamic world. Over the past 35 years, OKIhas made numerous efforts to solve this problem of Islamic Calendar unification. However, there efforts have been unsuccesfull. This study thus aims to explore further the efforts of unifying the Islamic Calendar for the Islamic world and to analyze efforts of internationalizing the Islamic Calendar by OKI. Research was conducted in qualitative methods by analyzing documents consistings of scholarly books, resolutions, and journals. The this study findingsincludes: in the last four decades, the International Islamic Calendarunification efforts is a divided into four phases and Internationally, and International Islamic Calendar unificationhas been conducted by OKI consistently. Sistem kalender Islam adalah unsur penting dalam peradaban Islam. Keberadaan kalender Islam sejak 14 abad lalu mempunyai fungsi penanda waktu berbagai hal kehidupan muslim seperti aktivitas ibadah dan muamalah. Namun sayingnya setelah digunakan 1. 400 tahun, system kalender Islam belum bias digunakan secara seragam di dunia Islam. Merespon permasalahan tersebut, sejak 35 tahun lalu OKI telah melakukan upaya-upaya penyatuan kalender Islam, akan tetapi upaya-upaya tersebut hingga kini belum berhasil. Kajian ini bemaksud menyoroti lebih jauh tentang usaha-usaha penyatuan Kalender Islam Internasional yang pernah dilakukan oleh OKI. Kajian ini dijalankan dengan metode kualitatif dan analisis dokumen dari rujukan buku-buku, resolusi-resolusi, dan jurnal-jurnal. Hasil penelitian ini di antaranya; dalam empat dekade terakhir, isu penyatuan Kalender Islam Internasional di dunia Islam terbagi menjadi empat fase dan secara hubungan internasional usaha penyatuan kalender Islam antara bangsa telah dijalankan oleh OKI secara konsisten.